(untitled) (Research, Society and Development, 2025)
Introduction: Autistic spectrum disorder (ASD) is a type of disorder that affects neurological development, being predominant with a higher incidence in males. It is included in the group of syndromes known as Pervasive Developmental Disorder - PDD. Objective: The aim of this study is to describe, through an integrative review, the benefits that aquatic activities can provide for children diagnosed with autism. Method: It is an integrative literature review. The databases used were: Pubmed, (SciELO) and the Virtual Health Library Portal (VHL). Initially, 25 articles were selected, of which only ten were excluded after reading them, five for not including water activities in the treatment of ASD, two for not being studies with children and three for being incomplete.Results: The aquatic environment presents itself as a good option for the development of motor intervention activities, in view of its physiological characteristics, which favor the execution of various movements that might not be possible to perform out of the water.Conclusion: Therefore, we conclude that the benefits provided to children with ASD through water activities are evident, since they provide benefits for the life of the child with autism that go beyond the physical, motor, cognitive and socio-affective scope, and can improve significantly the lives of children with the disorder.